Kreativitas Guru Dalam Mengenalkan Pancasila Pada Anak Usia Dini Di TK Aisyiyah Bustanul Athfal - Yunisar H. Baharuddin Baco; Ardini, Pupung Puspa; Laiya, Sri Wahyuningsi (Early Childhood Education Department, Faculty of Education, State University of Gorontalo, 2024)
The study formulation was to determine the teacher’s creativity in introducing Pancasila to pre-school kids TK Aisyiyah Bustanul Athfal Bolobungkang Village, Lobu District, Banggai Regency. This qualitative research was conducted in TK Aisyiyah Bustanul Athfal Bolobungkang Village Lobu District Banggai Regency. The study’s object was the teacher’s creativity in introducing Pancasila. Teacher creativity indicators in introducing Pancasila include creative ideas, innovative learning activities, educational media creation, and creative learning strategies. The research findings indicated that teachers use innovative media, including teaching aids, Pancasila puzzles, coloring Pancasila drawings, and national songs, to introduce Pancasila in daily life. In introducing the first principle of Pancasila, the teachers used strategies such as religious activities, whle the second principle is by fostering sensitivity and empathy among students towards their peers, whereas the third principle is by teaching students to respect and appreciate differences. Further, the teacher introduces the fourth principle of Pancasila by engaging students in discussions and asking about their preferences in choosing games to play, while the fifth principle is introduced by accustoming children to the queuing culture and guiding children not to disturb their peers’ rights.